BAHASA SUNDA DI JATINEGARA KAUM DAN PEMUKIMAN KETURUNAN PANGERAN ACHMAD DJAKETRA - Wati Kurniawati (BRIN, 1996)
Based on historical reviews, the speakers of Sundanese language are the descendants of Prince Achmad Djaketra and Prince Sugeri who used the title